Determination of Cell Proliferation and Apoptosis in Placentas of Chronically Stressed Rats - Cots, Debora Soledad (2013)
Chronic stress during gestation can alter several mechanisms that maintain homeostasis in the placenta. The aim of this study was to determine both effects of chronic stress on the apoptotic and cell proliferation processes in placentas of rats, during the second half of pregnancy and the immunolocalization of apoptotic and proliferating marked nuclei in the different placental zones. Stress by immobilization was applied to rats from the 4th day of pregnancy until their sacrifice on days 12, 17 or 21. Placental sections were immunolabeled with anti-BrdU and TUNEL. The apoptotic index did not present significant differences between control and stress groups. The gestational day influenced significantly on the apoptotic index, which showed a significant decrease on day 17 of gestation and significant increase on day 21. The proliferating index presented significant differences between gestational stages studied, which showed a significant increase at day 17 and then a significant decrease at day 21. Moreover, the stress treatment applied highly influenced on the proliferation index. In conclusion, chronic stress by immobilization did not produce effects on apoptotic process. However it produces an increase in cellular proliferation index in the three gestation days analyzed, which could generate a deleterious environment for the fetus development